Preferensi Mahasiswa Terhadap Buah Lokal Kabupaten Tuban: Preferensi Mahasiswa Terhadap Buah Lokal Kabupaten Tuban - Musyahida, Soviana (Journal Science Innovation and Technology (SINTECH), 2024)
Local fruits are one type of cultural diversity. In addition to functioning to meet food and vitamin needs, local fruits are also a characteristic of a particular region. Local fruits are fruits that grow naturally from a particular area. One effort to develop these local fruits is to introduce them to the wider community today. The purpose of this study was to determine the preferences of students of the Faculty of Agriculture, Sunan Bonang University, Tuban, towards local fruits in Tuban, namely siwalan, starfruit tasikmadu, longan merakurak, guava soko and duku prunggahan. This study was conducted using a survey method to 50 respondents using an online questionnaire. The results of the study of the preferences of students of the Faculty of Agriculture at Sunan Bonang University, Tuban, towards local Tuban fruits are Siwalan fruit because of its unique, sweet, and fresh taste, of course, a fruit that is very familiar in the Tuban area. The fruit that is preferred because of its distinctive taste is Tasikmadu Starfruit, although the seeds of the Tasikmadu starfruit are planted in other areas, the taste will definitely be different from the original fruit planted in Tasikmadu. For the fruit that is liked because of its sweet taste and is rarely found every season is Kelengkeng Merakurak. While the fruit that is liked because of its content or benefits is Guava Biji Soko because this fruit has a lot of vitamin C content which is good for the body. And the local fruit that is less liked by students of the Faculty of Agriculture is Duku Prunggahan because this fruit is not yet known to many people in Tuban.